The well-being age U-shape effect in Germany is not flat - David G. Blanchflower; Alan Piper (Global Labor Organization (GLO), 2021)
Kassenboehmer and DeNew (2012) claim that there is no well-being age U-shape effect for Germany, when controlling for fixed effects and respondent experience and interviewer characteristics in the German Socio-Economic Panel, 1994-2006. We re-estimate with a longer run of years and restrict the age of respondents to those under seventy and find the well-being age U-shape effect is neither flat nor trivial.
Keywords: I31; J14; C42; 330; age; ageing; life satisfaction; interviewer characteristics; interviewee experience; fixed effects; panel analysis; GSOEP